Dari Komuniti Ke Ekonomi Lestari: Menggerakkan Koperasi Dan Desa Menjadi Pusat Ekonomi Rakyat Yang Berdaya Saing - Alfian Sayuti; Arwin Yafi Rahmatullah; Juliana Palit; Khairunnisa; Endra Gunawan Aji Saputra (Universitas Mataram, 2026)
This community service activity was organized by the Faculty of Economics and Business, Universitas Bumigora, aiming to strengthen public and student understanding of sustainable economy concepts through cooperative-based community empowerment. The event was conducted online on November 1, 2025, under the theme “From Community to Sustainable Economy: Empowering Cooperatives and Villages as Competitive People-Centered Economic Hubs.” The activity featured two international speakers from Koperasi Keluarga Haji Roslan Kedah Berhad (Malaysia), namely Muhammad Najmuddin bin Mazlan and Muhamad Hafiz bin Muhamad Ahyat. The materials consisted of Module 1, which discussed social cooperatives and the Business Model Canvas (BMC) framework, and Module 2, which showcased practical examples of social enterprise development in Malaysian rural communities. Participants gained valuable insights into how cooperatives can serve as both economic and social entities that promote member welfare and community empowerment. The post-event evaluation showed that more than 90% of participants reported improved understanding of sustainable cooperative models and international collaboration opportunities. This program contributed to enhancing community economic literacy and fostering cross-country cooperation in digital cooperative and social entrepreneurship initiatives. Overall, it supports the achievement of the Sustainable Development Goals (SDGs), particularly Goal 8 (Decent Work and Economic Growth) and Goal 11 (Sustainable Communities).